The effect of course design on the number of rank shifts in skicross world cup for women and men - Tomelleri, L.; Mannsåker, I. H.; Lachaize, T.; Wortelboer, W.; Pfyffer, J.; Lasshofer, M.; Gilgien, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: In World Cup Skicross, athletes compete in heats of four to advance through a cup system to the big final, where the winner of the competition is crowned. The courses include terrain obstacles such as jumps, rollers, dragon backs, and turns of various types. The obstacles are built to challenge the technical, tactical, and physical abilities of the athletes, and to separate them from each other and to create a competition that is exciting to ski and exciting to watch. For the sport to be attractive to the athletes and spectators, the races should allow athletes to fight for their position throughout the course and change their ranking several times on their way from start to finish [1]. Therefore, course designers need to understand and build courses that provoke and allow athletes to frequently overtake each other. To gain quantitative knowledge on how course characteristics create opportunities for rank shifts between athletes within a heat, this study examined the relationship between course characteristics and rank shifts in Men and Women World Cup Skicross.